Intestine microbiota and neurodegenerative diseases: Can microbiota affect the brain? - Evelin F Meirelles; Matheus V Coste Grahl (Open Journal of Biological Sciences - Peertechz Publications, 2020)
The communication between the digestive tract and the brain is an important aspect to the regulation and maintenance of its functionality. This communication is made by a network of signals that the brain sends to the gastrointestinal tract and vice-versa through the gut-brain axis. These signals can be direct or indirect, direct is a signal sent by the pathogen to the brain, while indirect is a signal originated from the alterations that the pathogen triggers.